MENINGKATKAN KEMAMPUAN MENGENAL BILANGAN PADA ANAK KELOMPOK A MELALUI PERMAINAN KANTONG BILANGAN DI PAUD AZ-ZAHRA’ LEKOK - Latifah; Windasari, Indriana Warih (LPPM IAD Probolinggo, 2023)
This research aims to improve the number recognition game using number bags. This research uses Classroom Action Research, the subjects in this research are Group A children at PAUD AZ-ZAHRA' LEKOK, totaling 16 children. Based on the results of children's evaluation analysis regarding increasing the ability to recognize numbers through the number bag game, in the pre-cycle it was 15% for 3 children, then after using number recognition through the number bag game the percentage achieved in cycle I was 70% for 11 children, and the cycle II, the percentage increased, the percentage increased to 90% for 15 children. Therefore, it can be concluded that the number recognition activity is through the number bag game for Group A children at PAUD AZ-ZAHRA'LEKOK. Key words: games, number bags, recognizing number.